2023
DOI: 10.1091/mbc.e23-01-0014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Aurora B pools at the inner centromere and kinetochore have different contributions to meiotic and mitotic chromosome segregation

Abstract: Proper chromosome segregation depends on establishment of bioriented kinetochore-microtubule attachments, which often requires multiple rounds of release and reattachment. Aurora B and C kinases phosphorylate kinetochore proteins to release tensionless attachments. Multiple pathways recruit Aurora B/C to the centromere and kinetochore. We studied how these pathways contribute to anaphase onset timing and correction of kinetochore-microtubule attachments in budding yeast meiosis and mitosis. We find that the po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have revealed that there are several mechanisms that can recruit CPC-Aurora B or -Ipl1 to centromeres, kinetochores and mitotic spindles ( Bonner et al, 2019 ; Broad and DeLuca, 2020 ; Broad et al, 2020 ; Cairo et al, 2023 ; Campbell and Desai, 2013 ; Fischbock-Halwachs et al, 2019 ; Garcia-Rodriguez et al, 2019 ; Haase et al, 2017 ; Hadders et al, 2020 ; Liang et al, 2020 ; Marsoner et al, 2022 ). In our experiments, we did not attempt to distinguish between these different localization patterns of Ipl1, and instead we defined recruitment as concentrated localization between the SPBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that there are several mechanisms that can recruit CPC-Aurora B or -Ipl1 to centromeres, kinetochores and mitotic spindles ( Bonner et al, 2019 ; Broad and DeLuca, 2020 ; Broad et al, 2020 ; Cairo et al, 2023 ; Campbell and Desai, 2013 ; Fischbock-Halwachs et al, 2019 ; Garcia-Rodriguez et al, 2019 ; Haase et al, 2017 ; Hadders et al, 2020 ; Liang et al, 2020 ; Marsoner et al, 2022 ). In our experiments, we did not attempt to distinguish between these different localization patterns of Ipl1, and instead we defined recruitment as concentrated localization between the SPBs.…”
Section: Discussionmentioning
confidence: 99%
“…Bub1 kinase phosphorylates H2A threonine 120 (H2A Serine 121 in yeast) at kinetochore-proximal centromeres, which recruits shugoshin (Sgo1), providing a binding site for the borealin CPC component ( Kawashima et al, 2007 ; Peplowska et al, 2014 ; Tsukahara et al, 2010 ; Yamagishi et al, 2010 ). In addition to these interactions, other studies have shown CPC–Aurora B or Ipl1 recruitment to inner kinetochores via the COMA complex ( Cairo et al, 2023 ; Fischbock-Halwachs et al, 2019 ; Garcia-Rodriguez et al, 2019 ), and even to spindle microtubules ( Campbell and Desai, 2013 ). Despite the detailed information about these recruitment mechanisms, the biological contexts that induce Aurora B recruitment to centromeres remain less well understood.…”
Section: Introductionmentioning
confidence: 96%